Nutritional senolytics and senomorphics: Implications to immune cells metabolism and aging – from theory to practice - Luís, Carla; Maduro, Ana T.; Pereira, Paula; Mendes, José João; Soares, Raquel; Ramalho, Renata (Frontiers in Nutrition, 2022)
Ageing is a natural physiological process, but one that poses major challenges in an increasingly ageing society prone to greater health risks as diabetes, cardiovascular disease, cancer, frailty, increased susceptibility to infection and reduced response to vaccine regimens. The loss of capacity for cell regeneration and of the surrounding tissue microenvironment itself is conditioned by genetic, metabolic and even environmental factors, such as nutrition. The senescence of the immune system (immunosenescence) represents a challenge, especially when associated to the presence of age-related chronic inflammation (inflammaging) and affecting metabolic programming of immune cells (immunometabolism). These aspects are linked to poorer health outcomes and therefore present an opportunity for host-directed interventions aimed at both eliminating senescent cells and curbing the underlying inflammation. Senotherapeutics are a class of drugs and natural products that delay, prevent or reverse the senescence process – senomorphics; or inhibit senescence-associated secretory phenotype – senomorphics. Natural senotherapeutics from food sources – nutritional senotherapeutics, may constitute an interesting way to achieve better age-associated outcomes through personalised nutrition. In this sense, the authors present herein a framework of nutritional senotherapeutics as an intervention targeting immunosenescence and immunometabolism; identify research gaps in this area and gathered information on concluded and ongoing clinical trials on this subject. Also, we present future directions and ideation for future clinical possibilities in this field.